Significado funcional do gene de resposta precoce ao crescimento - EGR-1 - para a biologia do Orthopoxvírus Vaccinia - Patricia Nogueira da Gama Silva (2005)
Poxviruses are viruses that present a linear, double-stranded DNA genome and multiply exclusively in the cell cytoplasm, in both, vertebrates and invertebrates. The orthopoxvirus Vaccinia virus (VV), is the prototype of the Poxviridae family, having capacity to encode more than 200 gene products. MAPKs (mitogen activated protein kinases) are important mediators of signal transduction and have a crucial role in the regulation of several cellular functions such as growth, proliferation, differentiation and apoptosis. Due to this, several viruses, as part of their multiplication strategy, regulate the activation of different MAPKs, e.g., the hepatitis B virus, the coxsackievirus B3, the Influenza virus, the Epstein Barr virus and the VV, among others. One of the consequences of the MAPK signaling pathway activation, in particularly Ras/Raf/MEK/ERK/Elk, by mitogenic stimuli, is the expression of immediate early genes, including c-fos, c-jun and the early growth response gene (egr-1). Andrade et al. (2004) demonstrated that this signaling pathway is also stimulated by VV, leading to Egr-1 expression and being necessary for its mutiplication. Since the analysis of Egr-1 perfomed above did not contemplate all the viral multiplication cycle, we decided to do a more detailed study of it. We characterized Egr-1 expression (mensage and protein) in response to viral infection and verified that it iniciates 1 hour after infection and goes on until late times of infection, aproximately 36 hours after infection. We also verified that it is dependent of the multiplicity of infection (m.o.i.), “de novo” protein synthesis and of early expression of viral genes, and results of simultaneous stimulation of the signaling pathways involving MEK/ERK and serine-threonine kinases (STK). We also generated, selected and characterized cellular clones stably expressing, MEK-1 negative dominance and we were able to demonstrate that MEK/ERK is functionaly relevant, not only for the egr-1 expression induced by VV, but also for viral multiplication and viral plaque fenotype. To verify the functional significance of Egr-1 for the biology of this orthopoxvirus, we generated, selected and characterized cellular clones stably expressing, siRNA for Egr 1. We could demonstrate that this cellular protein, whose expression is regulated by the virus since early times of infection until late ones, is localized preferentially in the nucleus and has a crucial role in the multiplication economy of VV. The description of one signaling pathway, leading to the expression of cellular protein that affects multiplication and viral plaque fenotype, explicits the necessity of interaction of this microorganism with its host. Altogether, the results presented here, has no precedent in the literature of poxviruses.